2010
DOI: 10.1002/bit.22660
|View full text |Cite
|
Sign up to set email alerts
|

A process for microbial hydrocarbon synthesis: Overproduction of fatty acids in Escherichia coli and catalytic conversion to alkanes

Abstract: The development of renewable alternatives to diesel and jet fuels is highly desirable for the heavy transportation sector, and would offer benefits over the production and use of short-chain alcohols for personal transportation. Here, we report the development of a metabolically engineered strain of Escherichia coli that overproduces medium-chain length fatty acids via three basic modifications: elimination of β-oxidation, overexpression of the four subunits of acetyl-CoA carboxylase, and expression of a plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
244
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 218 publications
(253 citation statements)
references
References 48 publications
8
244
0
1
Order By: Relevance
“…Further steps to improve fatty acid production in E. coli include cytosolic expression of multifunctional fatty acyl-CoA synthetase (tesA 0 ) 4 and plant-derived fatty acyl-ACP thioesterases 6 to alleviate the feedback inhibition of b-ketoacyl-ACP synthase by the accumulated fatty acyl-ACPs 23 . Crude fatty acids were extracted, derivatized and analysed by gas chromatography mass spectrometry (GC-MS) (a representative chromatographic profile can be found in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further steps to improve fatty acid production in E. coli include cytosolic expression of multifunctional fatty acyl-CoA synthetase (tesA 0 ) 4 and plant-derived fatty acyl-ACP thioesterases 6 to alleviate the feedback inhibition of b-ketoacyl-ACP synthase by the accumulated fatty acyl-ACPs 23 . Crude fatty acids were extracted, derivatized and analysed by gas chromatography mass spectrometry (GC-MS) (a representative chromatographic profile can be found in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Early metabolic engineering studies on fatty acid production have been dedicated to optimizing precursor supply and the specificity of plant fatty acyl-ACP thioesterase 4,6,10,30,31 . Engineering the reversal of b-oxidation pathway 7 and a dynamic sensor-regulator system 32 have also led to the production of fatty-acid-derived long chain chemicals and fuels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key prerequisite is to maximize the specific activity of the fatty acid synthase (FAS) in the biotransforming microbe. Indeed, recent efforts have shown that genetic manipulation of the E. coli FAS can improve its productivity of free fatty acids and their derivatives (7,16,19,20). Notwithstanding these early successes, considerably greater improvements in atom economy and volumetric productivity are warranted, if fatty acid derivatives are to emerge as prominent fuels in the marketplace.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids also help maintain viability in response to temperature and environmental changes and can be targets for modification by reactive oxygen species or membrane-active agents (2)(3)(4)(5)(6)(7)(8). Fatty acids, or the products derived from them, are valuable as food additives, specialty chemicals, and petroleum substitutes (9)(10)(11)(12). Thus, there is considerable interest in understanding the suite of fatty acids that can be made by native or engineered pathways.…”
mentioning
confidence: 99%